Phytochemisty and Spermatogenic Potentials of Aqueous Extract of Cissus populnea (Guill. and Per) Stem Bark - Anthony B. Ojekale; Oladipupo A. Lawal; Adedoyin K. Lasisi; Tajudeen I. Adeleke (The Scientific World Journal)
In vivo clinical trials involving the administration of crude extracts of Cissus populnea to male subjects (normospermic, oligospermic, and azoopermic) in a 72-day study revealed that continuous exposure of the subjects to the extracts over this period did not significantly (p ≤ 0.05) alter sperm count, morphology, motility, or volume. Antimicrobial screening of the extract against some selected microbial isolates secondarily implicated in male infertility revealed total inactivity against the microbial isolates screened, i.e., Staphylococcus aureus, Salmonella paratyphi, Escherichia coli, Proteus mirabilis, Pseudomonas aeruginosa, Candida albicans, and Klebsiella sp. Phytochemistry revealed the presence of tannins, flavonoids, saponins, and steroids. The presence of these secondary metabolites was confirmed by thin layer chromatography. We conclude that oral administration of aqueous extracts of the stem bark of Cisssus populnea over a 72-day period to human subjects apparently had no fertility enhancement effects on sperm parameters monitored in this study.